Planos de texto e sequências textuais no gênero manifesto: perspectivas para o ensino da escrita argumentativa no Instituto Federal de Educação, Ciência e Tecnologia do Amapá - Gonçalves, Tatiana da Conceição (2022)
This study is part of the research line of Reading, text, and discourse in oral and writing modalities of the Post-Graduate Studies Program in the Portuguese Language at the Pontificia Universidade Católica de São Paulo, and its theme is the study of the manifesto as a perspective for teaching in argumentative writing, in particular, in the 3rd grade of integrated technical high school at the Instituto de Educação, Ciência e Tecnologia do Estado do Amapá. We assume as a hypothesis that the study of the text plan and the textual sequences that make up the manifesto genre opens perspectives for the teaching of argumentative writing in high school. Regarding this assumption, we defined the following research questions: 1) How are the text planes and text sequences organized in the manifesto genre? 2) What perspectives does the study of the manifesto, with regard to the textual plane and textual sequences, enable the teaching of argumentative writing? In order to answer these questions, we established as the main objective to analyze text plans and textual sequences in the manifesto genre and to reflect on their use in the teaching of argumentative text in high school. The specific objectives are: 1) identify, describe and analyze text plans and textual sequences in the manifesto genre and 2) reflect on how the text plans of the manifesto genre, in their different imbrications of textual sequences, can constitute an important strategy for the approach of argumentative writing in high school. From a theoretical point of view, we are based on the contribution of Textual Linguistics (FÁVERO; KOCH, 2012; KOCH, 2014, 2015; MARCUSCHI, 2012; MARQUESI, 2004; CAVALCANTE, 2014) and Textual Analysis of Discourses (ADAM, 2011, 2019; MARQUESI, 2017, 2018; MARQUESI; CABRAL, 2017; MARQUESI; ELIAS; CABRAL, 2017; MARQUESI; CABRAL; RODRIGUES, 2020; AGUIAR; MARQUESI, 2019; CABRAL, 2013, 2017). To deepen our approach, we deal with the arguments (ABREU, 2009; AMOSSY, 2018; CABRAL, 2017; 2018; FIORIN, 2015; MARQUESI; CABRAL; RODRIGUES, 2020; MEYER, 2008; KOCH; ELIAS, 2016; PERELMAN; OLBRECHTSTYTECA, 2014; PLANTIN, 2008), as well as we present some of the studies on the text (FÁVERO; KOCH, 2012; MARCUSCHI, 2008; MARQUESI; ELIAS; CABRAL, 2017). Regarding the manifest genre, we appealed to what guides the BNCC (2017), with regard to the study of texts claiming and denouncing disrespect for rights, and we discuss its characteristics (BORTULUCCE, 2015; MARX and ENGELS 2011; PÊGO, 2009; SANTOS, 2009). The corpus consists of five manifests, presented as examples. The results allow us to consider that the study of the compositional organization of the manifesto genre constitutes an important strategy for teaching argumentative writing, taking into account that when we identify, describe and analyze the text plans and the variations in the compositional structure of the manifesto, perceptible, especially, by the occurrence of textual sequences, we noticed that these elements favor the ordering of the argumentative movement, as well as the coherence inherent to the discursive purpose of this genre, which ins consolidated to its illocutionary aim